Molecular modeling of lactoferrin for food and nutraceutical applications: insights from in silico techniques - Kevion K. Darmawan; Tom C. Karagiannis; Jeff G. Hughes; Darryl M. Small; Andrew Hung (Critical Reviews in Food Science and Nutrition, 2023)

VPR-254: an inhibitor of ROR-gamma T with potential utility for the treatment of inflammatory bowel disease - Leo R. Fitzpatrick; Jeff Small; Robert O’Connell; George Talbott; Gordon Alton; Jim Zapf (Inflammopharmacology, 2020)

A centralized model for creating shared, standardized, microsatellite data that simplifies inter-laboratory collaboration - Jeff J. Stephenson; Matt R. Campbell; Jon E. Hess; Chris Kozfkay; Andrew P. Matala; Megan V. McPhee; Paul Moran; Shawn R. Narum; Melanie M. Paquin; Ora Schlei; Maureen P. Small; Donald M. Van Doornik; et al. (Conservation Genetics, 2009)

KILLER WHALES AND MARINE MAMMAL TRENDS IN THE NORTH PACIFIC—A RE‐EXAMINATION OF EVIDENCE FOR SEQUENTIAL MEGAFAUNA COLLAPSE AND THE PREY‐SWITCHING HYPOTHESIS - Paul R. Wade; Vladimir N. Burkanov; Marilyn E. Dahlheim; Nancy A. Friday; Lowell W. Fritz; Thomas R. Loughlin; Sally A. Mizroch; Marcia M. Muto; Dale W. Rice; Lance G. Barrett‐Lennard; Nancy A. Black; Alexander M. Burdin; et al. (Marine Mammal Science, 2007)
Springer et al . (2003) contend that sequential declines occurred in North Pacific populations of harbor and fur seals, Steller sea lions, and sea otters. They hypothesize that these were due to increased predation by killer whales, when industrial whaling's removal of large whales as a supposed primary food source precipitated a prey switch. Using a regional approach, we reexamined whale catch data, killer whale predation observations, and the current biomass and trends of potential prey, and found little support for the prey‐switching hypothesis. Large whale biomass in the Bering Sea did not decline as much as suggested by Springer et al ., and much of the reduction occurred 50–100 yr ago, well before the declines of pinnipeds and sea otters began; thus, the need to switch prey starting in the 1970s is doubtful. With the sole exception that the sea otter decline followed the decline of pinnipeds, the reported declines were not in fact sequential. Given this, it is unlikely that a sequential megafaunal collapse from whales to sea otters occurred. The spatial and temporal patterns of pinniped and sea otter population trends are more complex than Springer et al . suggest, and are often inconsistent with their hypothesis. Populations remained stable or increased in many areas, despite extensive historical whaling and high killer whale abundance. Furthermore, observed killer whale predation has largely involved pinnipeds and small cetaceans; there is little evidence that large whales were ever a major prey item in high latitudes. Small cetaceans (ignored by Springer et al .) were likely abundant throughout the period. Overall, we suggest that the Springer et al . hypothesis represents a misleading and simplistic view of events and trophic relationships within this complex marine ecosystem.

Microcosm Evaluation of the Fate, Toxicity, and Risk to Aquatic Macrophytes from Perfluorooctanoic Acid (PFOA) - Mark L. Hanson; Jeff Small; Paul K. Sibley; Tim M. Boudreau; Richard A. Brain; Scott A. Mabury; Keith R. Solomon (Archives of Environmental Contamination and Toxicology, 2005)